Defoliation of strawberry mother plants for the production of runner tips - Dal Picio, Miriane; Andriolo, Jerônimo Luiz; Cardoso, Francieli Lima; Lerner, Maíne Alessandra; Souza, Jéssica Maronez de (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to determine the sink‑source relationships and their effects on the number and growth of runner tips of 'Camino Real' strawberry stock plants. Three types of sources were evaluated: one defoliation at 96 days after planting (DAP), two defoliations at 50 and 96 DAP, and mother plants without defoliation. Four types of sink were accessed: runner tips collected weekly and monthly, four stolons with rooted runner tips in pots, and four freely-grown stolons. A completely randomized experimental design was used in a split-plot arrangement, with four replicates. The source types were placed in the plots, and sink types in the subplots. The number of runner tips, the crown diameter, and the dry matter mass were determined. Number and growth of tips were higher on plants without defoliation, and decreased 44.7% on twice‑defoliated mother plants. The two‑defoliation management did not reduce runner tip dry matter mass only on plants with rooted stolons, which produced runner tips 50% heavier. Defoliation of mother plants bearing rooting stolons can be used to reduce their growth, without reducing the emission and growth of runner tips.